Ischemic ECG Pattern Recognition to Facilitate Interpretation While Task Switching: A Parallel Curriculum - Caitlin Schrepel; Ashley E. Amick; Madeline Sayed; Anne K. Chipman (Association of American Medical Colleges, 2021)
Introduction Interruptions are an inevitable part of working as an emergency physician, yet these can increase cognitive load and precipitate medical error. Emergency physicians learn to balance these responsibilities using a process called task switching. Yet residents have little exposure to exercises that purposefully integrate task switching during their training. We addressed this gap by exposing emergency medicine (EM) trainees to task-switching events in the form of critical ECG interpretation while they were engaged in concurrent, parallel activities. Methods The curriculum was carried out in three phases. First, 12 PGY 2 residents engaged in a small-group session testing their baseline confidence and ECG interpretation skills. The second phase was longitudinal: During concurrent educational activities, investigators interrupted tasks and asked trainees to interpret ECGs in 10 seconds or less. The curriculum's final phase was used to review the ECGs and answer any questions. Results Confidence and percentage of correct interpretations were compared from phase 1 to phase 2. Participants showed improved confidence (M = 2.5, SD = 0.6, to M = 2.9, SD = 0.6; p = .02; 5-point Likert scale) and increased mean percent correct (M = 0.7, SD = 0.1, to M = 0.8, SD = 0.1; p = .01) following the curriculum. Discussion Our curriculum provides a pragmatic, reproducible approach to enhancing critical ECG interpretation with task switching in a way that mirrors the EM practice environment, promoting a reduction of cognitive load and highlighting the skills learners will need as they develop expertise.